The Process of Social Research - Dixon, Jeffrey C.; Singleton, Royce; Straits, Bruce C. (New York : Oxford University Press, 2019)
Featuring a conversational, engaging, and student-friendly writing style, The Process of Social Research, Second Edition, introduces students to the fundamentals of research. It places a unique emphasis on process with flowcharts in every chapter that provide step-by-step guides for conducting social research and evaluating the research of others. Authors Jeffrey C. Dixon, Royce A. Singleton, Jr., and Bruce C. Straits use relatable, everyday examples and carefully selected research examples to make the book accessible to undergraduates. Comprehensive and up-to-date without attempting to be encyclopedic in its coverage, The Process of Social Research provides a balance between qualitative and quantitative research, taking a more integrated approach to describing the relationship between theory and research.
Keywords: Social sciences -- Methodology -- Research